A lived-experience investigation of narratives: recycled drinking water. Issue 4 (3rd July 2016) - Ching, Leong
Abstract: Recycled drinking water (RDW) represents a cost-effective and technologically reliable source of urban water. Yet it remains one of the least implemented solutions because of emotional and psychological difficulties – the human dimension of the 'yuck factor', which has been empirically identified as statistically significant. Researchers have therefore recently expanded water research in RDW to include the psychology of users. This study builds on this effort by using the lived-experience methodology for the first time on RDW. Investigating the case of Singapore, the method reveals an 'insider's view' of key stakeholders, and uncovers human-scale narratives and experiences within the discourses of technology, economics of water supply, and ecological realities.